How do you divide and simplify \frac { x ^ { 2n} + 5x ^ { n} - 6} { x ^ { 2n} + 9x ^ { n} + 18} \div \frac { x ^ { 2n} - 1} { x ^ { 2n } + 7x ^n + 12}?

1 Answer
May 22, 2017

(x^n+4)/(x^n+1).

Explanation:

Let, x^n=y," so that, "x^(2n)=y^2.

Hence, The Expression

=(y^2+5y-6)/(y^2+9y+18)-:(y^2-1)/(y^2+7y+12),

=((y+6)(y=1))/((y+6)(y+3))-:((y-1)(y+1))/((y+4)(y+3)),

=((cancel(y+6))(cancel(y=1)))/((cancel(y+6))(cancel(y+3)))xx((y+4)(cancel(y+3)))/((cancel(y-1))(y+1)),

=(y+4)/(y+1),

=(x^n+4)/(x^n+1).